2019
DOI: 10.3390/toxins11120718
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Morphology, Aflatoxin Production, and Virulence of Aspergillus flavus by the Major Nitrogen Regulatory Gene areA

Abstract: Aspergillus flavus is a renowned plant, animal and human pathogen. areA is a global nitrogen regulatory gene of the GATA transcription factor family, shown to be the major nitrogen regulator. In this study, we identified areA in A. flavus and studied its function. The AreA protein contained a signatory zinc finger domain, which is extremely conserved across fungal species. Gene deletion (∆areA) and over-expression (OE::areA) strains were constructed by homologous recombination to elucidate the role of areA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…In A. flavus: areA was recently identified in A. flavus and demonstrated to be partially involved in aflatoxin production. The lack and overexpression of areA resulted in increased/decreased amounts of aflatoxin depending on the nitrogen source media [111]. The direct implication of AreA in aflS expression has been demonstrated in the presence of different sources of nitrate and ammonium [112].…”
Section: Demonstration Of the Connection With Af/st Synthesismentioning
confidence: 99%
“…In A. flavus: areA was recently identified in A. flavus and demonstrated to be partially involved in aflatoxin production. The lack and overexpression of areA resulted in increased/decreased amounts of aflatoxin depending on the nitrogen source media [111]. The direct implication of AreA in aflS expression has been demonstrated in the presence of different sources of nitrate and ammonium [112].…”
Section: Demonstration Of the Connection With Af/st Synthesismentioning
confidence: 99%
“…Similarly, if ROS is applied in vitro, aflatoxin production can be stimulated [47], such as aflatoxin biosynthesis stimulated by H 2 O 2 in A. flavus [31]. Previous studies have shown that several transcription factors have been involved in oxidative stress and secondary metabolism, including numerous bZIP-type TFs [29,48,49]. In aspergilli, Yap1 orthologs were reported as the coregulator of oxidative stress response with secondary metabolism, such as napA in A. nidulans, Aoyap1 in A. ochraceus, Apyap1 in A. parasiticus, and Afap1 in A. flavus [6,9,10,31].…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins like aflatoxins, trichothecenes, and structurally related toxins are major concerns in food contamination because of their high toxicity to mammals (Arunachalam and Doohan, 2013;Fasoyin et al, 2019;Luciano-Rosario et al, 2020). However, many of these fungal SM also contribute to plant colonization and pathogenicity.…”
Section: Non-traditional Effectors and Host-selective Toxins (Hsts)mentioning
confidence: 99%